A randomized controlled trial to examine the impact of a multi-strain probiotic on self-reported indicators of depression, anxiety, mood, and associated biomarkers - Walden, Kylie E.; Moon, Jessica M.; Hagele, Anthony M.; Allen, Leah E.; Gaige, Connor J.; Krieger, Joesi M.; Jäger, Ralf; Mumford, Petey W.; Pane, Marco; Kerksick, Chad M. (Frontiers in Nutrition, 2023)
Objective: To examine the efficacy of supplementing with a multi-strain probiotic (MSP) on changes associated with mood, anxiety, and neurotransmitter levels. Method: In a randomized, double-blind, placebo-controlled fashion, 70 healthy men and women (31.0 ± 9.5 years, 173.0 ± 10.4 cm, 73.9 ± 13.8 kg, 24.6 ± 3.5 kg/m2) supplemented with a single capsule of MSP (a total daily dose of 4 x 109 colony forming units [CFU] comprised of a 1 x 109 CFU dose from each of the following strains: Limosilactobacillus fermentum LF16, Lacticaseibacillus rhamnosus LR06, Lactiplantibacillus plantarum LP01, and Bifidobacterium longum 04 (Probiotical S.p.A., Novara, Italy) or a maltodextrin placebo (PLA). After 0, 2, 4, and 6 weeks of supplementation and 3 weeks after ceasing supplementation, study participants completed the Beck Depression Inventory (BDI-II), State-Trait Anxiety Inventory (STAI), and Leiden Index of Depression Sensitivity (LEIDS-R) questionnaires and had plasma concentrations of cortisol, dopamine, serotonin, and C-reactive protein determined. Results: BDI, STAI, and total LEIDS-R scores were reduced from baseline (p < 0.05) with MSP supplementation after 4 and 6 weeks of supplementation and 3 weeks after supplementation while no changes (p > 0.05) were reported in PLA. When compared to PLA, MSP scores for state anxiety, trait anxiety, and LEIDS-R (hopeless, aggression, rumination, and total score) were significantly lower (p < 0.05) after supplementation. Plasma serotonin concentrations in MSP were increased from baseline after 6 weeks of supplementation and 3 weeks after ceasing supplementation. No changes (p > 0.05) in plasma dopamine, C-reactive protein, or cortisol concentrations were observed between groups. Conclusion: MSP supplementation resulted in widespread improvements in several questionnaires evaluating mood, anxiety, and depression in young, healthy men and women. MSP supplementation increased serotonin increased after 6 weeks of MSP supplementation with no change in dopamine, C-reactive protein, or cortisol.